2019
DOI: 10.1111/ijn.12737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of message‐framed informational videos on diabetes management knowledge and self‐efficacy

Abstract: Aim Nurses play an essential role in improving health‐related knowledge and self‐efficacy of patients through health education. This study aimed to investigate the effects of message‐framed informational videos on diabetes management knowledge and self‐efficacy in patients with type 2 diabetes. Methods A quasi‐experimental pretest and posttest design with two experimental and one standard care comparison groups was carried out to examine the effects of the message‐framed videos. The two message‐framed informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 35 publications
2
28
1
Order By: Relevance
“…By following the impact that other people have, the patient will always try to achieve his beliefs. This is in line with the research conducted using animated video interventions, which showed pictures that positively impacted the intervention group in diabetes patients in maintaining the health of their feet (16).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By following the impact that other people have, the patient will always try to achieve his beliefs. This is in line with the research conducted using animated video interventions, which showed pictures that positively impacted the intervention group in diabetes patients in maintaining the health of their feet (16).…”
Section: Discussionsupporting
confidence: 89%
“…Using animation, positive examples were given to the intervention group, and negative examples were given to the control group. This intervention was designed and validated by an endocrinologist, diabetes nurse educator (16).…”
Section: Indirect Educational Mediamentioning
confidence: 99%
“…Total 2253 articles were systematically retrieved, after removing duplicate literature and screening the titles and abstracts, with 42 articles were read the full text. A total of 11 studies was included: 23 32–41 10 RCTs and 1 quasi-experimental study 33 based on previously established inclusion and exclusion criteria. Figure 1 illustrates the PRISMA flow chart of the literature screening process.…”
Section: Resultsmentioning
confidence: 99%
“… 23 32 34–36 39 40 Only four studies were set up in three groups: a gain-framed group, a loss-frame group and a standard control group for providing usual care, with no message framing. 33 37 38 41 The gain-framing condition highlighted the positive outcomes of completing or adhering to healthy behaviour, whereas the loss-framing condition emphasised the undesirable consequences of failing to comply or adhere to healthy behaviour, which corresponded with the positive-framing outcomes. Messages were delivered via video, pamphlets and online.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the self-efficacy of T2DM patients was 2.42 ± 0.59, remaining a moderate level. Some previous studies showed that educational interventions for patients are known to be effective in increasing self-efficacy, which is vital to influence the adequacy of patients' self-management [ 37 , 38 ]. Self-efficacy was positively correlated with reducing complication risk, improving foot care, and developing diet or food plan in DM knowledge in our study ( r = 0.163, 0.146, 0.121; P ≤ 0.001, respectively), demonstrating that patients with high GSE scores paid more attention to acquire related knowledge and to positively manage DM.…”
Section: Discussionmentioning
confidence: 99%